An Ir(III) complex chemosensor for the detection of thiols. Issue 1 (1st December 2016) - Mao, Zhifeng; Liu, Jinbiao; Kang, Tian-Shu; Wang, Wanhe; Han, Quan-Bin; Wang, Chun-Ming; Leung, Chung-Hang; Ma, Dik-Lung
Abstract: In this study, we report the use of a cyclometalated luminescent iridium(III) complex for the visualization of thiols. The detection of glutathione (GSH) by complex1 is achieved through the reduction of its phendione N^N donor, which influences the metal-to-ligand charge-transfer (MLCT) of the complex. Complex1 produced a maximum threefold luminescence enhancement at 587 nm in response to GSH. The linear detection range of1 for GSH is between 0.2 and 2 M equivalents of GSH, with a detection limit of 1.67 μM. Complex1 also displays good selectivity for thiols over other amino acids. Abstract :